2008
DOI: 10.4314/ajcem.v9i2.7490
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalent Bacterial Isolates Of Dental Caries In School Age Children Attending The Dental Clinic Of Oauthc, Ile-Ife

Abstract: The study was conducted at the dental clinic of Obafemi Awolowo University Teaching Hospital Complex, Ile-Ife. A total of 100 carious samples were collected from children of varying age and sexes. The bacteria isolated were S. mutans: 45.6%, Lactobacillus spp: 41.2% and S. aureus: 13.2%. Out of the 100 samples, 88(5) had mixed growth of bacteria and the common bacteria combinations were S. mutans and Lactobacillus spp.(43.2%) , S. mutans and.S. aureus (38.6%) and Lactocillus spp and S. aureus (18.2%)The distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
2
2
Order By: Relevance
“…In the current study, the predominant isolate bacteria were Streptococcus mutans with 46.4%. The findings of this study were consistent with other studies conducted in Nigeria (45.6%) [ 16 ] and Nepal (43.7%) [ 38 ]. And the current study shows more Streptococcus mutant isolate than the previous studies conducted in India (22.8%), Nepal (40%) [ 30 , 37 ], and Nigeria (18.7%) [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, the predominant isolate bacteria were Streptococcus mutans with 46.4%. The findings of this study were consistent with other studies conducted in Nigeria (45.6%) [ 16 ] and Nepal (43.7%) [ 38 ]. And the current study shows more Streptococcus mutant isolate than the previous studies conducted in India (22.8%), Nepal (40%) [ 30 , 37 ], and Nigeria (18.7%) [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…In other contrast, this finding was lower than the study done in Debre Birhan (68.7%) [25]. Other than S. mutans isolate, our study shows 35.2% prevalence of Staphylococcus aureus which is higher than other studies conducted in Nepal (31.6%) and Nigeria (28.9%) [15,16,38]. The difference might be due to the methodology, socioeconomic backgrounds, dietary behaviors, and differences in knowledge and practice regarding the tooth brushing habit.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…: 41.2% and S. aureus: 13.2%. Their studies the researcher conclude that the antibiotic Ceftriaxone, Ciprofloxacin, Perfloxacin and Chloramphenicol are the most successful besides the caries-inducing organisms with a standard vulnerability series of 76.1% to 92.2% [17]. This result mismatched with the present invent found that the isolated 20 Lactobacillus spp.…”
Section: Mar Index For Isolates =contrasting
confidence: 60%
“…In this study, adhesion profiles of three bacterial ( Pseudomonas aerigunosa , Staphylococcus aureus and Eschereshia coli ) strains have been tested against three relatively newly developed commercial dental restorative materials. Two of these strains ( Pseudomonas aerigunosa and Staphylococcus aureus ) are linked to biofilm formation on dental materials and the natural tooth surface and they are associated with incidences of primary and secondary caries development [ 11 , 20 , 21 ]. Escherichia coli can be remotely involved in progression of dental diseases, especially in patients with chronic gastritis and acid reflux [ 22 ].…”
Section: Introductionmentioning
confidence: 99%